PERAKITAN KLON UBIJALAR UNTUK HASIL PROTEIN TINGGI - Sri Umi Lestari; Nur Basuki (BUANA SAINS, 2007)
The research that was aimed to create a new variation on sweet potato population was conducted at 2003 and 2004. Crossing between two introduction clones (Beniazuma and BIS-214) as a parent of bearing tuber-protein content genes with five clones of tuber high yield potential, was obtained 1157 genotypes of new hybrid F1. The selection result found 168 new clones having minimum yield as 0.5 kg/plant or  20 ton/ha and 3% tuber protein content on dry weight basis. Among 168 clones there were 21 genotypes with protein yield range from 1.0-2.5 ton protein content/ha